An FFT-Based Companding Front End for Noise-Robust Automatic Speech Recognition. (26th June 2007) - Raj, Bhiksha; Turicchia, Lorenzo; Schmidt-Nielsen, Bent; Sarpeshkar, Rahul
Abstract : We describe an FFT-based companding algorithm for preprocessing speech before recognition. The algorithm mimics tone-to-tone suppression and masking in the auditory system to improve automatic speech recognition performance in noise. Moreover, it is also very computationally efficient and suited to digital implementations due to its use of the FFT. In an automotive digits recognition task with the CU-Move database recorded in real environmental noise, the algorithm improves the relative word error by 12.5% at− 5 dB signal-to-noise ratio (SNR) and by 6.2% across all SNRs (− 5 dB SNR to+ 15 dB SNR). In the Aurora-2 database recorded with artificially added noise in several environments, the algorithm improves the relative word error rate in almost all situations.